PERSONAL ORIENTATION OF PREPARATION OF THE FUTURE TEACHERS IN CONDITIONS OF CONTINUOUS FORMATION(EDUCATION) AND INTEGRATION INTO THE INTERNATIONAL EDUCATIONAL SYSTEM - Kondrashova, L.V. (Pedagogy of Higher and Secondary Education, 2007)
New paradigm of education is expressed in tendency to its «humanization», humanizing of educational sphere, changing of student’s position from an object to a subject of a training process. The problem of quality education, promoted by Bologna Declaration, can’t be successfully solved without the transition of the system of continuous educational-discipline training to personal-oriented pedagogical process in Higher School. The article deals with the conditions of transforming social-professional experience into a personal plan of activity.